Communication interventions for medically unexplained symptom conditions in general practice: A systematic review and meta-analysis of randomised controlled trials - Byrne, Ailish Katherine; Scantlebury, Arabella; Jones, Katherine; Doherty, Laura; Torgerson, David J. (PLOS ONE, 2022)
Background Medically unexplained symptoms (MUS) account for 3–50% of all General Practitioner (GP) consultations and are difficult to diagnose due to their unknown aetiology, symptom overlap between conditions, and lack of effective treatment options. MUS patients’ and primary care clinicians frequently face challenges during consultations, with GPs reporting difficulty identifying and classifying MUS, whilst patients report stigma and feeling illegitimised by clinicians. Communication interventions have been proposed as a method to facilitate the doctor-patient relationship and aid the management of MUS. Aim This systematic review aims to evaluate the effectiveness of primary care based communication interventions at improving MUS patients’ and/or clinician outcomes. Method Four electronic databases were searched from inception to November 2021. Two researchers independently undertook screening, data extraction and quality appraisal. Given the heterogeneous nature of the studies identified, narrative syntheses were conducted, along with meta-analyses where possible to pool data. Results 9 papers from 10 Randomised Controlled Trials were included. The included studies displayed considerable risk of bias and poor reporting. Some limited evidence suggests that communication interventions tailored to MUS and not following a pre-specified model (such as reattribution) could improve pain, mental and physical functioning whilst reattribution training may improve clinician confidence treating MUS. However, methodological limitations mean that these findings should be interpreted with caution. Conclusion A range of interventions for improving communication with MUS patients in primary care have been evaluated. However, the heterogeneous nature of existing evidence and poor study quality mean we cannot conclude whether these interventions are effective. Before considering further randomised controlled trials researchers should focus on developing a new or modified communication intervention for MUS patients and their clinicians. Trail registration The systematic review was prospectively registered with PROSPERO (registration record CRD42020206437).